Variabilidade espacial de atributos do solo e da produtividade da soja e qualidade do solo em sistema de integração lavoura-pecuária - Silva, Francine Damian da (2015)
For the sustainability of integrated crop-livestock systems, the proper management of its components (soil-plant-animal), which are dynamic and interact with each other, are essential to define the system's ability to provide positive or negative carbon balance to system and determine the physical, chemical and biological soil, which can affect the production capacity of agricultural soils. The objective of this study was to characterize the spatial and temporal variability of soybean yield and understand their relationship with the spatial variability of dungs, physical properties and chemical soil, and soil quality in different grazing intensities in integrated crop-livestock system. Chapter I concluded that the soil organic C stocks under different grazing intensities was related to indices of soil quality. The highest C stratification ratio and C pool index were found in the treatment with moderate grazing intensity. The integrated crop livestock system acts as source or sink of atmospheric C depending on the grazing intensity. Under heavy grazing intensity, the system acts as a source (0.04 Mg ha−1yr−1), and under light grazing intensity, it acts as a sink. The value range from 0.25 to 0.37 Mg ha−1yr−1.Pastures managed at 0.20 and 0.40 m sward height had the best balance between CMI and animal daily weight gain. The best balance between C management index and live weight gain per unit area, C management index and economic return, occurred in sward height of 0.20 m. Chapter 2 concluded that the dung supply affects the cycling of the nutrients P and K in the soil, in comparison with sites without supply, and the pasture height of 10 cm treatment had the highest P content in the soil in relation to the treatment of 0.40 m. The average diameter of the aggregates was higher with 0.40 m in relation to the treatment of 0.10 m and soil density was similar between the heights of the pasture. Treatment of sward height 0.10 m, which had a more homogeneous distribution of dungs in the area, showed greater variability of nutrients P and K, and the treatment of 0.40 m, which had the lowest number of dungs with distribution concentrated in attractive points, had the lowest variability of nutrients. In years with severe water restriction, all pasture height treatments were affected, with an average yield reduced by 80% over 2012/13 and 2013/14 crops without water restriction. The main components affected by water stress were the number of pods per plant and the weight of 1000 grains (2011/12). For the year severe water restriction the sward height of 0.40 m treatment, which provided greater coverage contribution dead on the ground, had the highest soybean yield variability.